The influence of the thermomechanical processing on the annealing response of 3CR12 steel - Matheson, Ian Murdo (Centre for Materials Engineering, 2016)
An investigation was performed on alloys of a 12wt% Cr steel (3CR12) that had undergone different thermomechanical processing routes prior to the annealing step of production. The aim of this research was to identify any changes in the annealing response of 3CR12 steel due to the different thermomechanical processing routes to which the alloys had been subjected. Three alloys of 3CR12 were subjected to various cooling treatments immediately following hot rolling. This was accomplished by water quenching, air cooling and insulatory cooling of the hot-rolled plates. Characterisation of the alloys in the hot-rolled and annealed conditions included optical and electron microscopy, macro- and microhardness tests, tensile tests and impact energy tests, dilatometry, differential thermal analysis and volume fraction analysis. Alloys in the as-rolled state exhibited an increase in martensite content related to an increase in the cooling rate following hot rolling. The increase in martensite content inﬂuenced the alloys' mechanical properties by raising their bulk hardness, UTS and yield strength. This was coupled with a decrease in the elongation and impact toughness of the alloys. Furthermore, the Ac1 was found to increase with higher cooling rates following hot rotting. Variations in the as-rolled microstructures influenced the alloys' subsequent annealing response, with there being a greater and more immediate response to the annealing treatment by alloys subjected to higher cooling rates after hot rolling. The fully annealed alloys showed little variation in their microstructures or mechanical properties, despite clear variations in their as-rolled microstructures.